Challenges in Human Resource Management:Paradigm Shift - Aurora, Rajinder; Gupta, Silpy (SFIMAR Research Review, 2015)
Human Resource Management (HRM) is all about designing the management systems to ensure that human talent of an organization is used effectively and efficiently to accomplish organizational goals. People in organizations can be a core competency. This core competency becomes the strength and forms the foundation for creating a competitive advantage for on organization. Thus managing people as human resources is essential in organizations of all sizes and types. The generation of the entire workforce is changing manifold with changes in their habits, likes, needs, etc. As a field, HRM is also undergoing significant transformation to cope up with the challenges. This paper talks about the alteration which is taking place in HRM processes and the challenges the new system is facing in today’s dynamic environment. The paper recommends ways to take care of the challenges faced by the untested HRM practices.